Oxford Reading Tree:Floppy's Phonics: Sounds and Letters: Book 30 - Roderick Hunt (India Oxford University Press, USA, 2011)
The Stage 5 Sounds and letters books show sounds, graphemes and alternative spellings and pronunciations from Phase 5 of Letters and Sounds in the context of Oxford Reading Tree scenes.
Keywords: Read Aloud -- Read Aloud